Rethinking Edutourism in Indonesia: A Systematic Review of Global Evidence and Policy Implications - Mustafa, Rizki Handayani; Supriyanto, Budi; Rianty, Rilla; Nismara, Muhammad Inas; Sitanggang, Igras Vigran Antonio (Lasigo Akademia Indonesia, 2025)
Edutourism is gaining momentum globally as a transformative learning paradigm that integrates education, tourism, and socio-cultural development. Unlike traditional study tours, edutourism emphasizes experiential learning, critical reflection, and contextual immersion. In Indonesia, however, the development of edutourism is hindered by fragmented regulations, geographical disparities, and limited institutional capacity. This study uses a Systematic Literature Review (SLR) and bibliometric analysis of 88 peer-reviewed articles published between 2016 and 2025, sourced from Scopus and Google Scholar, to identify key trends in global edutourism practices. The analysis reveals seven thematic clusters: ecological awareness, governance, rural resilience, cultural identity, spatial efficiency, social impact, and policy innovation. Findings suggest that successful edutourism models globally are driven by cross-sectoral policy integration, collaborative governance, and pedagogical alignment with local contexts. In Indonesia, overcoming challenges such as uneven infrastructure and funding gaps requires a phased, locally grounded approach. To advance edutourism, pilot-based strategies that emphasize decentralization, digital integration, and alignment with the Sustainable Development Goals (SDGs) offer a more effective path forward than national mandates.